Programed death-1/programed death-ligand 1 expression in lymph nodes of HIV infected patients: results of a pilot safety study in rhesus macaques using anti–programed death-ligand 1 (Avelumab). (23rd October 2016) - Gill, Amanda L.; Green, Samantha A.; Abdullah, Shahed; Le Saout, Cecile; Pittaluga, Stefania; Chen, Hui; Turnier, Refika; Lifson, Jeffrey; Godin, Steven; Qin, Jing; Sneller, Michael C.; Cuillerot, Jean-Marie; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The programed death-1 (PD1)/programed death-ligand 1 (PD-L1) pathway plays a critical role in balancing immunity and host immunopathology. During chronic HIV/SIV infection, there is persistent immune activation accompanied by accumulation of virus-specific cells with terminally differentiated phenotypes and expression of regulatory receptors such as PD1. These observations led us to hypothesize that the PD1/PD-L1 pathway contributes to the functional dysregulation and ineffective viral control, and its blockade may be a potential immunotherapeutic target. Methods: Lymph node biopsies from HIV-infected patients ( n = 23) were studied for expression of PD1 and PD-L1. In addition, we assessed the safety and biological activity of a human anti-PD-L1 antibody (Avelumab) in chronically SIV-infected rhesus macaques. Results: PD-L1 expression was observed in cells with myloid/macrophage morphology in HIV-infected lymph nodes. Administration of anti-PD-L1 was well tolerated, and no changes in body weights, hematologic, or chemistry parameters were observed during the study. Blockade of PD-L1 led to a trend of transient viral control after discontinuation of treatment. Conclusion: Administration of anti-PD-L1 in chronic SIV-infected rhesus macaques was well tolerated. Overall, these data warrant further investigation to assess the efficacy of anti-PD-L1 treatment on viral control in chronic SIV infection as a prelude to such therapy in humans.